Pelatihan Kegiatan Pengembangan Diri Tari Indang Di SMK Negeri 3 Padang - Firmadanni Liska; Nerosti Nerosti; Desfiarni Desfiarni (FBS Universitas Negeri Padang, 2020)
The research aims to describe the process of training self-development activity of Indang Dancein SMK Negeri 3 Padang. This type of research is qualitative research using descriptive methods of analysis. The main instrument in this research is its own researchers and assisted with supporting instruments such as stationery and cameras. Data types use primary data and secondary data. Data collection techniques are conducted by way of library studies, observation and documentation. The steps for analyzing data are data reduction, data model (data display) and withdrawal/conclusion verification. The results showed that the training of the self-development activities of Indang Dance in SMK Negeri 3 Padang goes well, in the implementation of self-development activities Dance Indang students get a variety of experiences, students are also able to establish cooperation and solidarity well. The activity of self-development of Indang Dance in SMK Negeri 3 Padang is implemented by demonstration method, drill, Tekhnik enquiries (group exercises) with an imitation approach. Competence achieved by students in the training of the activities of self-development in the Indang Dance SMK Negeri 3 Padang is good. It can be seen from the number of students who have very good competence is as many as 12 students with a percentage of 75.00%, and 4 students have good competence with a percentage of 25.00%.